High Titer Ethanol and Lignosulfonate Production from SPORL Pretreated Poplar at Pilot Scale - Zhou, Haifeng; Zhu, J. Y.; Gleisner, Roland; Qiu, Xueqing; Horn, Eric (Frontiers in Energy Research, 2015)
Poplar NE222 (Populus deltoides Bartr. ex Marsh × P. nigra L.) wood chips were pretreated in a 390 L pilot-scale rotating wood-pulping digester using a dilute sulfite solution of approximately pH  1.8 at 160°C for 40 min for bioconversion to ethanol and lignosulfonate (LS). An estimated combined hydrolysis factor (CHF) of 3.3 was used to scale the pretreatment temperature and time from laboratory bench scale experiments, which balanced sugar yield and inhibitor formation to facilitate high titer ethanol production through fermentation using S. cerevisiae YRH400 without detoxification. A terminal ethanol titer of 43.6 g L-1 with a yield of 247 L tonne wood-1 was achieved at total solids loading of 20%. The relatively low ethanol yield compared with yield from SPORL-pretreated softwoods was due to inefficient utilization of xylose. The LS from SPORL has a substantially higher phenolic group (Ph-OH) content although it is less sulfonated and has a lower molecular weight than a purified commercial softwood LS, and therefore has potential for certain commercial markets and future novel applications through further processing.